Kajian Organologi Alat Musik Saluang Pauh Buatan Zulmasdi di Kota Padang - Try Wahyu Purnomo; Sri Mustika Aulia (Gondang: Jurnal Seni dan Budaya, 2020)
This paper discusses the materials, manufacturing methods and techniques used in making the Saluang Pauh instrument (Zulmasdi version). This study uses a qualitative approach that is descriptive, where the researcher can explain the process of making Saluang Pauh with the study of organology as a basis for analyzing the object. The results of the research refer to the technical theory of organology which includes measurement instruments, descriptions, depictions with scales or photographs, methods or techniques for making and analyzing the sound produced. The conclusion of this research can be seen that in making Saluang Pauh, Zulmasdi uses traditional techniques (in terms of cutting materials, making, measuring and drying instruments) combined with modern techniques (using digital media such as the tuning of the instrument tone) to produce innovative traditional instruments that in accordance with the development of the supporting community